2010
DOI: 10.1074/jbc.m110.152942
|View full text |Cite
|
Sign up to set email alerts
|

The Hippo Tumor Pathway Promotes TAZ Degradation by Phosphorylating a Phosphodegron and Recruiting the SCFβ-TrCP E3 Ligase

Abstract: The TAZ transcription co-activator promotes cell proliferation and epithelial-mesenchymal transition. TAZ is inhibited by the Hippo tumor suppressor pathway, which promotes TAZ cytoplasmic localization by phosphorylation. We report here that TAZ protein stability is controlled by a phosphodegron recognized by the F-box protein ␤-TrCP and ubiquitylated by the SCF/CRL1 ␤-TrCP E3 ligase. The interaction between TAZ and ␤-TrCP is regulated by the Hippo pathway. Phosphorylation of a phosphodegron in TAZ by LATS pri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

18
419
1
3

Year Published

2011
2011
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 447 publications
(455 citation statements)
references
References 35 publications
18
419
1
3
Order By: Relevance
“…PP1A Stabilizes TAZ by Decreasing the Interaction between TAZ and ␤-TrCP-Our recent work has shown that LATS and CK1 phosphorylate TAZ and promote TAZ interaction with the SCF E3 ubiquitin ligase and degradation (15). If PP1A dephosphorylates TAZ, it should stabilize TAZ by antagonizing the effect of LATS.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…PP1A Stabilizes TAZ by Decreasing the Interaction between TAZ and ␤-TrCP-Our recent work has shown that LATS and CK1 phosphorylate TAZ and promote TAZ interaction with the SCF E3 ubiquitin ligase and degradation (15). If PP1A dephosphorylates TAZ, it should stabilize TAZ by antagonizing the effect of LATS.…”
Section: Resultsmentioning
confidence: 99%
“…2C). Our recent study identified ␤-TrCP as a TAZ-binding protein to recruit the SCF E3 ubiquitin ligase (15). We then determined the effect of PP1A on the interaction between TAZ and ␤-TrCP.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations